Different faces of Mycoplasma pneumoniae in children - cardiological and skin complications- case reports and literature review - Zuzanna Piasecka; Kinga Knop-Chodyła; Ewelina Wesołek- Bielaska; Anna Kochanowska- Mazurek; Aneta Głaz; Marzena Pliszka; Agnieszka Kuzio; Aleksandra Cieplińska; Kinga Ziojła-Lisowska; Grzegorz Jama (Nicolaus Copernicus University in Toruń, 2024)
Mycoplasma pneumoniae is one of the main pathogens responsible for atypical pneumonia, especially in children over the age of 5, where it accounts for about 40% of cases of extramedullary pneumonia. In addition to respiratory-related symptoms, it can lead to a variety of extrapulmonary manifestations associated with involvement of other organs. In this article, we present case reports of two pediatric patients with detected M. pneumoniae infection with associated cardiac and skin complications. The first case report describes an 11.5-year-old boy who was admitted to the Department of Pediatrics because of chest pain, fever and moist cough for several days, who was diagnosed with myocarditis during M. pneumoniae infection. The second case report describes a 17-year-old girl with a recent respiratory infection who was admitted to the hospital for pain, swelling, blistering of the lips and oral mucosa. Mycoplasma pneumoniae infection can lead to extrapulmonary complications in children, which can produce nonspecific symptoms, so clinical vigilance and early recognition are important to minimize the risk of complications.